Best Practice in War-to-Peace Transition : The Uganda Veterans Assistance Program - World Bank (Washington, DC, 2012)
Veterans and their dependents constituted a particularly vulnerable group due to their lack of civic awareness, low skill level and few resources, a culture of dependency, and their potential threat to security. The Uganda Veterans Assistance Program (UVAB) assistance consisted of three components: demobilization, reinsertion assistance (a transitional safety net cash equivalent to meet basic needs for a six-month period or one crop-growing season) and reintegration (in particular counseling and training). In conjunction with the general availability of land, the reinsertion assistance provides the means for the successful economic reintegration of the majority of veterans and their families. Social reintegration proved more difficult, and many veterans had to overcome initial community resentment and mistrust, despite sensitization activities involving high-ranking government officials. The communities finally accepted the returning veterans as, contrary to their expectations, only few have shown antisocial behavior. The crime rate among veterans is below the national average, and in many cases, the presence of veterans has actually improved the security situation. While it is too early to determine whether the long-term reintegration of veterans has been achieved, the recently completed program is widely hailed as a success. Political will, needs-based planning and donor coordination through the World Bank culminated in timely and effective program completion.